2022
DOI: 10.1155/2022/9864411
|View full text |Cite
|
Sign up to set email alerts
|

Pseudogene MSTO2P Interacts with miR-128-3p to Regulate Coptisine Sensitivity of Non-Small-Cell Lung Cancer (NSCLC) through TGF-β Signaling and VEGFC

Abstract: Background. Coptisine has been widely used for treating a variety of cancer types. To date, whether pseudogene is implicated in coptisine resistance of NSCLC remains unknown. Methods. We performed MTT to assess the cell viability of A549 and Calu-1 cells. The transwell assay was used to examine the invasion of cells. TUNEL was used to determine apoptosis. Results. Our data showed that coptisine treatment suppressed cell viability and invasion of NSCLC cells while contributing to apoptosis. MiR-128-3p negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“… 28 miR-128-3p mimic could significantly influence the expression of SMAD2, SMAD5 and SMAD9 in non-small cell lung cancer A549 cell line. 29 To determine whether SMAD5 is a direct binding gene of miR-128-3p, the miR-128-3p inhibitor or mimic was transfected in cells containing MUT sequence and the WT sequence of SMAD5 through a luciferase reporter assay. It revealed that miR-128-3p inhibitor significantly increased the luciferase intensity and miR-128-3p mimic significantly decreased the luciferase intensity of SMAD5-WT when those were compared with the control group; however, no significant effect was found on the luciferase intensity of SMAD5-MUT ( Figure 7A and B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 miR-128-3p mimic could significantly influence the expression of SMAD2, SMAD5 and SMAD9 in non-small cell lung cancer A549 cell line. 29 To determine whether SMAD5 is a direct binding gene of miR-128-3p, the miR-128-3p inhibitor or mimic was transfected in cells containing MUT sequence and the WT sequence of SMAD5 through a luciferase reporter assay. It revealed that miR-128-3p inhibitor significantly increased the luciferase intensity and miR-128-3p mimic significantly decreased the luciferase intensity of SMAD5-WT when those were compared with the control group; however, no significant effect was found on the luciferase intensity of SMAD5-MUT ( Figure 7A and B ).…”
Section: Resultsmentioning
confidence: 99%
“…However, miR-128-3p inhibitor significantly promoted the expression of SMAD2, SMAD5 and SMAD9. 29 However, whether miR-128-3p could regulate MGO nanocomposites mediated BMSCs osteogenic behaviors via regulating SMAD5 has not been fully clarified. Interestingly, we found that circAars overexpression could positively improve SMAD5 activity and the miR-128-3p negatively manage the level of SMAD5.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudogene MSTO2P is found to be implicated in several diseases including lung cancer 32 , colorectal cancer 33 , etc. MSTO2P could function as a miR-128-3p sponge in non-small cell lung cancer cells (NSCLC), and MSTO2P /miR-128-3p to regulate coptisine sensitivity of NSCLC cells via TGF- β pathway.…”
Section: Resultsmentioning
confidence: 99%
“…EMT occurs mainly in various physiological and pathological processes, including tissue and embryonic development, organ injury and repair, organ fibrosis, metastasis of cancerous tumors, and other events. The pathway controls various cellular processes, such as cell specialization, programmed cell death, and cell growth, and has been demonstrated to hinder or facilitate the advancement of tumors through various mechanisms [16] . Dysfunction or atypical stimulation of TGF-β may result in various pathological disorders, such as cancerous growths, fibrotic ailments, aberrant immune reactions, and more.…”
Section: Acknowledgementmentioning
confidence: 99%